2019
DOI: 10.3324/haematol.2018.207928
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt-like lymphoma with 11q aberration: a germinal center-derived lymphoma genetically unrelated to Burkitt lymphoma

Abstract: Burkitt-like lymphoma with 11q aberration is characterized by pathological features and gene expression profile resembling those of Burkitt lymphoma but lacks the MYC rearrangement and carries an 11q-arm aberration with proximal gains and telomeric losses. Whether this lymphoma is a distinct category or a particular variant of other recognized entities is controversial. To improve the understanding of Burkitt-like lymphoma with 11q aberration we performed an analysis of copy number alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 31 publications
5
79
0
Order By: Relevance
“…The differences in the clinical presentation of MYC breakpoint‐positive BL and mnBLL,11q found in our study support the concept that both diseases share similar histopathological and immunophenotypical features, 3,10 but differ strikingly in molecular genetic features 5,6 . Given the fact that mnBLL,11q molecularly differ from typical BL, and that according to the data in this study Burkitt‐like lymphomas show excellent outcome under current NHL‐BFM treatment, mnBLL,11q may also be considered as a subgroup of lymphomas for dose‐reduction.…”
Section: Discussionsupporting
confidence: 83%
“…The differences in the clinical presentation of MYC breakpoint‐positive BL and mnBLL,11q found in our study support the concept that both diseases share similar histopathological and immunophenotypical features, 3,10 but differ strikingly in molecular genetic features 5,6 . Given the fact that mnBLL,11q molecularly differ from typical BL, and that according to the data in this study Burkitt‐like lymphomas show excellent outcome under current NHL‐BFM treatment, mnBLL,11q may also be considered as a subgroup of lymphomas for dose‐reduction.…”
Section: Discussionsupporting
confidence: 83%
“…The duplications/deletions in both cases encompass the minimal gain region, containing the candidate oncogene PAFAH1B 2, and the minimal loss region, containing candidate genes, FLI1 and ETS1 , as reported 13 16. Both cases show 6q deletion, the most common recurrent copy number abnormality other than those of 11q 19. The additional cytogenetic abnormalities not previously described for this entity include focal higher level 11q gain/amplification segments shown in both cases, a gain of 13q31.3 in case 1, a biallelic loss at 19p13.3p13.2, distal 4 p loss and distal 16q gain in case 1, and several large regions of copy-neutral loss of heterozygosity in case 1.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, recent studies suggest that LMO2 also appears to be useful for the differential diagnosis of BL and the provisional category of Burkitt-like lymphoma with 11q aberration. Two independent studies characterizing Burkitt-like lymphoma with 11q aberration, noted LMO2 protein expression in 7/10 (70%) and 5/11 (46%) cases [31,32]. An additional study including 75 BL observed absent expression of LMO2 in 74 (99%) cases, whereas three out of three Burkitt-like lymphomas with 11q aberration were positive [33].…”
Section: Discussionmentioning
confidence: 98%